Clinical Findings of the Oral Cavity in Outpatient Pulmonary Tuberculosis Patients at RSUD Kota Tangerang - Sarah Mersil; Fitri Zakiyah; Rani Handayani (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2025)
Introduction: Tuberculosis (TB) is one of the 9th world’s deadliest chronic infectious diseases caused by mycobacterium tuberculosis and predominantly affects the lungs. TB could also occur in other sites of the body, such as the oral cavity. The oral manifestation incidence of TB is approximately 0,1%–0,5%. Despite being a rare occurrence, oral TB remains a challenging issue because of its nonspecific clinical presentation. This study aims to determine the clinical findings of the oral cavity in outpatient’s pulmonary TB at RSUD Tangerang city. Materials and Methods: This research is a descriptive analysis with a cross-sectional study design. The data was collected with a total sample was 50 medical record’s of outpatient’s pulmonary TB at RSUD Tangerang City, both male and female, aged >18 years, who were visiting pulmonary unit, then were consulted to the oral medicine unit. We collected data about sociodemographic, TB diagnosis, and oral diagnosis Results and Discussions : The results showed that 18 sample had a very low DMF-T category (>5). The clinical findings of the oral cavity statistically showed that the third incidence highest percentage was chronic gingivitis (31,7%), coated tongue (17,6%), and atrophy glossitis (7,7%). Conclusion: The results suggest that outpatient’s with pulmonary TB have oral lesions with a varied clinical manifestations and very low caries experience.